Sistema de gestión académica e implementación de un ambiente virtual de aprendizaje del idioma inglés coadyuvado por tecnología WEB, a través de la herramienta OPEN SOURCE MOODLE para el Instituto de Idiomas "THE CANADIAN HOUSE CENTER", de la Ciudad de Loja. - Morocho Palacios, Henry Fabricio (2010)
The phenomenon of globalization and new technologies have helped improve the living conditions of man, and in turn have complicated ways of relating, communicating, and understanding ourselves. In this situation the public and private institutions are in constant evolution and renovation to stay innovative and be able to meet the current demands of the basis and growing demand of students who possess the Occupational English Language."The Canadian House" needs to develop and implement an Academic Management System and a Virtual Learning Environment for the English Language English Language Occupational Center" The Canadian House" considers it to be relevant and necessary to have a computerized, lead and present an orderly registration of students information, allocation of workload, registration and control by providing scholarships to students, pension payments and transcripts, among others. Also, to optimize the use of Information Technology and Communication, which can transmit, process and disseminate information instantly through a virtual learning environment that would provide access to all content and material needed to achieve the basic skills needed to study the English language. In the present in terms of mainly theoretical find information concerning: the history of the Occupational Center "The Canadian House Center" and what are the main problems that generated the need to implement the Academic Management System and the Virtual Learning Environment, also is moodle, its importance, the architecture handles, what are the advantages and disadvantages of its use, among others. Regarding the development of the alternative proposal can be observed: as has been achieved the objectives of the research, what were the requirements of the center will develop the system, which use cases were found with their respective description, domain model The entity relationship model and class diagram developed to provide the solution required by the entity. In the final part of this will be: the validation tests conducted both admin users, and users with the role of teachers and students. Also included are the various conclusions and recommendations that were made to achieve as a result of research carried out in the Occupational Center "The Canadian House Center.